The Prevalence of Dental Caries in Smokers and Smokeless Tobacco Users - Nallan CSK Chaitanya; Mamata Boringi; Ramakrishna Madathanapalle; Alekya Renee; Surabi V Sree; Nancy Priyanka; Triken Sownetha; Kondaiah Marella (Wolters Kluwer Medknow Publications, 2018)
Introduction: To assess the prevalence of dental caries in smokers and smokeless tobacco (ST) users and compare it with that of nonusers. Materials and Methods: A sample of 549 patients of both genders within 18-75 years, visiting the Department of Oral Medicine and Radiology, were categorized as follows: Group A-199 patients who smoked tobacco, Group B-150 patients who use ST, and Group C-200 patients with no habit of tobacco usage. A clinical examination of dental caries was conducted using Black's criteria, and habit duration, frequency, form, and the type of tobacco used were recorded. The obtained data were statistically analyzed by Kruskal-Wallis analysis of variance with post-hoc Conover test using the Statistical Package for the Social Sciences software. Results: The study revealed a higher prevalence of dental caries in the control group (mean-2.78) followed by the group with ST usage (mean-2.36) and then the group with smokers (mean-2.23), with the age range within 26-35 years having statistical significance of P < 0.001. In all the three groups, the prevalence of dental caries was more among males rather than females. Conclusion: There was a high prevalence of caries in control patients followed by ST users when compared to the group with smoking habit. The higher presence of caries in the ST usage group might be due to the presence of sweeteners in tobacco-chewing agents. Caries prevalence was less among smokers probably to thiocyanate (anticariogenic) activity in their saliva.